Scholarship between Europe and the Levant : Essays in Honour of Alastair Hamilton - Loop, Jan,; Kraye, Jill, (The History of Oriental Studies ;, 2020)
Scholarship between Europe and the Levant is a collection of essays in honour of Professor Alastair Hamilton. His pioneering research into the history of European Oriental studies has deeply enhanced our understanding of the dynamics and processes of cultural and religious exchange between Christian Europe and the Islamic world. Written by students, friends and colleagues, the contributions in this volume pay tribute to Alastair Hamilton's work and legacy. They discuss and celebrate intellectual, artistic and religious encounters between Europe and the cultural area stretching from Northern Africa to the Arabian Peninsula, and spanning the period from the sixteenth to the late nineteenth century. Contributors: Asaph Ben-Tov, Alexander Bevilacqua, Maurits H. van den Boogert, Charles Burnett, Ziad Elmarsafy, Mordechai Feingold, Aurélien Girard, Bernard Heyberger, Robert Irwin, Tarif Khalidi, J.M.I. Klaver, Noel Malcolm, Martin Mulsow, Francis Richard, G. J. Toomer, Arnoud Vrolijk, Nicholas Warner, Joanna Weinberg, and Jan Just Witkam.